2020
DOI: 10.1371/journal.pone.0229283
|View full text |Cite
|
Sign up to set email alerts
|

Short chain fatty acids produced by colonizing intestinal commensal bacterial interaction with expressed breast milk are anti-inflammatory in human immature enterocytes

Abstract: Necrotizing enterocolitis (NEC) is a devastating intestinal emergency that affects ten percent of very low birth weight premature babies and costs society in both expense and heartache. It is probably caused by an inappropriate interaction of colonizing bacteria with an immature intestine. A possible preventative measure is to feed prematures their mother's expressed breast milk in conjunction with a probiotic. This synbiotic prevention reduces the severity and incidence of this condition. This study was desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 31 publications
2
43
0
Order By: Relevance
“…The SCFAs produced by Bifidobacterium spp. exert anti-inflammatory activities in mature enterocytes and immunocytes through the G-protein-coupled receptor and by inhibiting histone deacetylase 4 and 5 [ 47 ]. A previous study also demonstrated that stress and infection could result in a significant decrease in the SCFA-producing genera, such as Butyricimonas , Anaerostipes , Butyricicoccus , Coprococcus , and Parabacteroides [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…The SCFAs produced by Bifidobacterium spp. exert anti-inflammatory activities in mature enterocytes and immunocytes through the G-protein-coupled receptor and by inhibiting histone deacetylase 4 and 5 [ 47 ]. A previous study also demonstrated that stress and infection could result in a significant decrease in the SCFA-producing genera, such as Butyricimonas , Anaerostipes , Butyricicoccus , Coprococcus , and Parabacteroides [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…The immature intestine may respond differently to SCFAs than the mature intestine. While SCFAs have demonstrated anti-inflammatory effects on human fetal organoids and fetal mouse intestine [117], butyrate appears to trigger NEC-like lesions in germ-free lactose-fed quails [118] and in a piglet NEC model, formula containing fermented E. coli had high levels of acetate and propionate and was associated with NEC-like lesions [119]. Tryptophan in human milk is metabolized by gut microbes, including B. longum ssp infantis, into indole-3-lactic acid, which binds to the aryl-hydrocarbon receptor in immature intestinal tissue and inhibits the pro-inflammatory cytokine IL8 [120].…”
Section: Mechanismsmentioning
confidence: 99%
“…SCFAs generated by probiotics interfere with pathogenicity by reducing intestinal pH, destroying pathogen cell membrane structure, accelerating oxidative phosphorylation, enhancing the antibacterial potential of other molecules (68), regulating the expression of histone deacetylase, and coupling with G protein receptors (71). In addition, SCFAs blocks secretion of IL-8 and macrophage inflammatory protein 2 by intestinal IL-1b in naive mice, evidencing the characteristic anti-inflammatory effect of SCFAs (72). Moreover, probiotics improve immunity by stimulating IgA production through the following mechanisms: (a) triggering the activation of TLR9 and TLR2, (b) promoting DCs maturation, (c) regulating B lymphocytes, (d) being involved in mucosa cytokines production, and (e) inducing the release of TGF-β, IL-10, and IL-6 (68, 71).…”
Section: Anti-infection and Anti-inflammatory Roles Of Probioticsmentioning
confidence: 99%